Calcium Imaging of Nerve-Mast Cell Signaling in the Human Intestine - Buhner, Sabine; Barki, Natasja; Greiter, Wolfgang; Giesbertz, Pieter; Demir, Ihsan E.; Ceyhan, Güralp O.; Zeller, Florian; Daniel, Hannelore; Schemann, Michael (Frontiers in Physiology, 2017)
Introduction: It is suggested that an altered microenvironment in the gut wall alters communication along a mast cell nerve axis. We aimed to record for the first time signaling between mast cells and neurons in intact human submucous preparations. Methods: We used the Ca2+ sensitive dye Fluo-4 AM to simultaneously image changes in intracellular calcium [Ca+2]i (%F/F) in neurons and mast cells. Data are presented as median with interquartile ranges (25%/75%). Results: We recorded nerve responses in 29 samples upon selective activation of 223 mast cells by IgE receptor cross linking with the antibody mAb22E7. Mast cells responded to mAb22E7 with a median [Ca+2]i increase of 20% (11/39) peaking 90 sec (64/144) after the application. Only very few neurons responded and the median percentage of responding neuronal area was 0% (0/5.9). Mast cell activation remained in the presence of the fast sodium channel blocker tetrodotoxin. Specific neuronal activation by transmural electrical field stimulation in 34 samples evoked instantaneously [Ca+2]i signals in submucous neurons. This was followed by a [Ca+2]i peak response of 8%F/F (4/15) in 33% of 168 mast cells in the field of view. The mast cell response was abolished by the nerve blocker tetrododoxin, reduced by the Calcitonin Gene-Related Peptide receptor 1 antagonist BIBN-4096 and the Vasoactive Intestinal Peptide receptor antagonist PG97‐269, but not by blockade of the neurokinin receptors 1-3. Conclusion: The findings revealed bidirectional signaling between mast cells and submucous neurons in human gut. In our macroscopically normal preparations a nerve to mast cell signaling was very prominent whereas a mast cell to nerve signaling was rather rare.